Revisiting "Twilight of the Gatekeepers": Resurrection. Issue 5 (September 2021) - Rowe, Sylvia; Alexander, Nick
Abstract : In recent years, nutrition, health, and other science communicators have noted a dramatic change among the disseminators, the purveyors of the information that is their stock in trade. Evolution of the information landscape has been dramatic as it morphs from traditional media—peer-reviewed print journals and science articles in newspapers, broadcast television, and radio—to more technologically modern media. The present authors have documented the passing of the "old guard" of health and science communication "gatekeepers, " as newer digitally based information increases—exponentially. However, although the traditional curation of information may have experienced a significant decrease, the authors argue that new gatekeepers have emerged to take on the task. The present article analyzes the transition of journal and other print editors, as well as academic and other traditionally educated scientists, to the new cyber curators of health and science news. The resulting implications for today's communicators are also explored.